Mutant-IDH1-dependent chromatin state reprogramming, reversibility, and persistence - Turcan, S̨evin (Nature genetics, 2018)
This study uses human astrocytes and glioma tumorspheres to generate an atlas of mutant-IDH1-induced epigenomic reprogramming. The findings have implications for understanding mutant IDH function and for optimizing approaches to target IDH-mutant tumors.
Gesehen am 17.09.2018
Article was first published on 27 November 2017